Research on the Application of Blackboard Writing Images in College English Writing Teaching Aided by "POA" Theory. (26th August 2022) - Du, Haixia
Abstract : English is the most widely used language in the world as an official language and the most widely used language in the world as a second language. Writing ability is one of the five basic skills of English learners. Writing a beautiful English article has high requirements on the learners' thinking, vocabulary, grammar, organization, and appropriateness. Research shows that for most English learners, English writing is the most difficult, and learners generally have problems in writing, such as incoherent expression, poor logic, single structure, and lack of interest. In addition, the domestic English writing teaching mode still has the problem of "ignoring the output and focusing on the input", which leads to poor teaching effect and the students' writing level cannot be effectively improved. In response to the above problems, this paper proposes to design a college English writing teaching plan based on the output-oriented approach (POA), focusing on the three core teaching links of driving, facilitating, and evaluating. Analytical research is conducted. Experiments show that the effectiveness of blackboard writing image teaching and English writing teaching under the theory of "production-oriented approach" has been significantly improved.